Comparison of nalbuphine and morphine as intrathecal adjuvant to 0.5% bupivacaine for post-operative analgesia in lower abdominal surgeries – A randomized and control study - Subha Devanathan; Ilango Ganesan; Rangarajan R; Divya Devanathan (Asian Journal of Medical Sciences, 2024)
Background: The use of a higher volume of 0.5% bupivacaine, however, is associated with hemodynamic instability. Adjuvants such as morphine and other opioids are added in with the local anesthetic to reduce this adverse effect and extend the duration of sensory block, hence extending the length of analgesia. However, opiates are associated with a high risk of respiratory depression and other side effects. Nalbuphine has been used to counteract these adverse effects. Thus, we decided to compare the analgesic effect of intrathecal (IT) nalbuphine with IT morphine. Aims and Objectives: The aim of the study was to compare IT morphine with nalbuphine as adjuvant to a spinal anesthetic agent. The primary objective was to compare between the time of onset of sensory and motor blockade and the post-operative analgesic duration between the two adjuvants, while hemodynamic variables and side effects were studied as secondary variables. Materials and Methods: This randomized controlled study was conducted after Ethical Committee approval for a period of 1 year on 100 patients who fulfilled the inclusion criteria. They were randomized into two groups to receive sub-arachnoid block: Group A: 3 mL of 0.5% Hyperbaric Bupivacaine and 0.2 mg morphine and Group B:3 mL of 0.5% Hyperbaric Bupivacaine and 0.5 mg nalbuphine. The following parameters were monitored – Height, Weight, blood pressure, American Society of Anesthesiologists grading, time of onset, maximum duration and regression of Motor and sensory blocks, and total duration of analgesia. Results: The onset of sensory blockade was comparable in both groups while the onset of motor blockade was significantly longer in the morphine group (P≤0.001). The duration of analgesia in the morphine group was longer as compared to nalbuphine group and was statistically significant (P<0.05). The incidence of side effects was 26% in the morphine group and 6% in the nalbuphine group, which was statistically significant (P<0.05). Fourteen patients in the morphine group had pruritus and four patients in the nalbuphine group experienced nausea. Conclusion: IT nalbuphine with 0.5% bupivacaine produces rapid onset of anesthesia and early post-operative analgesia with minimal side effects, but the total analgesic duration was more with IT morphine.